2002
DOI: 10.1002/bem.110
|View full text |Cite
|
Sign up to set email alerts
|

Use of spot measurements for assessing residential ELF magnetic field exposure: A validity study

Abstract: The purpose of this study was to evaluate residential short term "spot" measurements as surrogates for long term personal magnetic field (MF) exposure. In an epidemiological study on birth weight and pregnancy delay, MF exposure was assessed by taking five spot measurements in each room. For a subsample of 30 subjects 24 h personal MF measurements were made, and the following exposure metrics were calculated: 24 h arithmetic mean, 24 h median, percentage of time above 0.15 microT, and percentage of time above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In the reference apartments on other floors, only one (3.3%) reading equal to or higher than 1 mT (1.30 mT) was found. The whole apartment mean, which has been shown to be the best spot-measurement-based metric for predicting personal 24-h exposure [Eskelinen et al, 2002], was at least 0.2 mT in all apartments above transformer stations. This value was reached in 10 first floor reference apartments (36%) and in only 3 reference apartments (10%) on other floors.…”
Section: Resultsmentioning
confidence: 99%
“…In the reference apartments on other floors, only one (3.3%) reading equal to or higher than 1 mT (1.30 mT) was found. The whole apartment mean, which has been shown to be the best spot-measurement-based metric for predicting personal 24-h exposure [Eskelinen et al, 2002], was at least 0.2 mT in all apartments above transformer stations. This value was reached in 10 first floor reference apartments (36%) and in only 3 reference apartments (10%) on other floors.…”
Section: Resultsmentioning
confidence: 99%
“…Rankin et al (2002) reported a Spearman correlation of 0.74 between point-in-time MF measurements and personal exposures, but the personal exposure measurement was limited to exposure in the home. Studies on the correlation of spot measurements with total 24 h personal exposure have shown correlations from 0.37 to 0.77 for timeweighted average exposure (Armstrong et al, 2001;Eskelinen et al, 2002) and from 0.41 to 0.74 for threshold-type exposure metrics (Eskelinen et al, 2002). It is of interest that, in the present data, the correlations with total 24 h exposure are not generally lower than those with the 12 h spent at home.…”
Section: Resultsmentioning
confidence: 40%
“…However, the 20-min measurements were not better than spot measurements for predicting long-term average exposure. For example, the residence-specific mean of spot measurements produced Spearman correlations of 0.77 for arithmetic mean, and 0.62 for median of the 24-h measurement (Eskelinen et al, 2002), which are higher than the correlations shown in Table 1. Also, the sensitivities and specificities (Table 1) were lower for the 20-min measurements than those found for the spot measurements (Eskelinen et al, 2002).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…for example, the known spatial variability of EMF exposure combined with movement of the person for whom exposure is estimated can have non-trivial consequences (Savitz, 1995;Miller and Green, 2010), and for this population has been shown to have low to high correlation with 24-hr personal exposure, depending on the location of sampling (Eskilen et al 2002). Similarly, expert assessment of occupational EMF exposure is notoriously difficult (Kheifets et al 2009;Savitz, 1995;Miller and Green, 2010), while the inference of personal EMF exposure from appliances based on self-reported information is also known to be subject to considerable error (Savitz, 1995).…”
mentioning
confidence: 99%